A new species of Moenkhausia Eigenmann, 1903 (Characiformes, Characidae) from the rio Amazonas basin, Brazil - Oliveira, Gustavo D.; Marinho, Manoela M. F. (Zootaxa, 2016)
Moenkhausia abyss is herein described from the rio Amazonas basin lowlands. The new species can be distinguished from the congeners by presenting the combination of the following characters: a dark blotch located on the upper caudal-fin lobe and the lower lobe hyaline, 25–29 branched anal-fin rays, humeral spot rectangular, vertically oriented, extending horizontally through two or two and a half scales and located over the third to the fifth lateral line scales, five longitudinal scale rows above the lateral line, predorsal scales arranged in a single not interrupted median row and 30–34 perforated lateral line scales. Brief comments on Moenkhausia megalops are provided.